MODEL PEMILIHAN RUTE DAN PEMBEBANAN PERJALANAN DENGAN SISTEM FUZZY - Cahyo Kresnanto, Nindyo; Z. Tamin, Ofyar; Bona Frazila, Russ (Jurnal Transportasi, 2009)
Route selection is a major element of the network assignment model. This process is often also callednetwork tree building. In conventional route selection, each repetition will only produce one best path orshortestpath. Using fuzzy systems approach, travel cost is modeled in fuzzy numbers. Fuzzy numbers arenumbers with certain upper-bound and under-bound limits. In fuzzy conditions, route selection process isexpected to produce several routes that can be nominated as the shortestpath. It means that in each repetition,the finding algorithm will generate more than one best route, starting from the first best route, the second bestroute, to the k best route. The next process is the trip assignment existing (demand side) on the transportationnetwork system (supply side) which will produce a route pattern and traffic flow. Traffic flow allocationbased on the series of best routes and degree of membership of fuzzy numbers.Keywords: fuzzy travel cost, fuzzy shortest path, fuzzy assignment